2021
DOI: 10.1007/s00477-021-02098-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of robustness of hybrid artificial neural network with artificial bee colony and firefly algorithm in predicting COVID-19 new cases: case study of Iran

Abstract: As an ongoing public health menace, the novel coronavirus pandemic has challenged the world. With several mutations and a high transmission rate, the virus is able to infect individuals in an exponential manner. At the same time, Iran is confronted with multiple wave peaks and the health care system is facing a major challenge. In consequence, developing a robust forecasting methodology can assist health authorities for effective planning. In that regard, with the help of Artificial Neural Network-Artificial B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Overfitting is a common issue with ANN models, where the model tends to learn noise in the data rather than the actual signals, leading to poor performance on untested datasets. To mitigate this, K-fold cross-validation is employed as a robust method [ 44 , 45 ]. In this technique, the data is randomly divided into K groups.…”
Section: Methodsmentioning
confidence: 99%
“…Overfitting is a common issue with ANN models, where the model tends to learn noise in the data rather than the actual signals, leading to poor performance on untested datasets. To mitigate this, K-fold cross-validation is employed as a robust method [ 44 , 45 ]. In this technique, the data is randomly divided into K groups.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with ARIMA, the hybrid approach indicated a lower error rate. A combination of the neural network with firefly and bee algorithms has been proposed for modeling the COVID-19 daily cases [ 39 ]. Based on the results, it can be concluded that both models were the robust forecaster of the pandemic in various countries.…”
Section: Introductionmentioning
confidence: 99%
“…The ascendancy of ABC and FA over other common meta-heuristic algorithms (e.g., genetic algorithm and particle swarm optimization) in unravelling myriad problems has been highlighted by various studies [ [49] , [50] , [51] , [52] , [53] ]. Moreover, these algorithms have demonstrated a robust accuracy rate in predicting the COVID-19 cases in the country level [ 39 ]. Therefore, the objective of this study is to develop the ANN-FA and ANN-ABC for predicting COVID-19 confirmed cases by considering the vaccinated population.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the prediction accuracy, researchers introduced intelligent models. For COVID-19 prediction, researchers have chosen artificial neural network (ANN) ( Shaibani et al, 2021 , Adnan et al, 2022 ), support vector machine (SVM) ( Challab and Mardukhi, 2021 , Kwak and Soo, 2020 ), extreme learning machine (ELM) ( Cui et al, 2021 ), kernel extreme learning machine (KELM) ( Shi et al, 2021 ), long short-term memory (LSTM) ( Luo et al, 2021 , Rauf et al, 2021 ). The above intelligent models improve the prediction effect to some extent, but the selection of parameters is artificial and uncertain, and the prediction effect is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“… The prediction effect is limited. Multiple linear regression model ( Alemu, 2020 ) Logistic regression model ( Elhag et al, 2021 ) Intelligent model ANN ( Shaibani et al, 2021 ) The prediction effect is greatly improved. To some extent, the prediction effect is improved, but the selection of parameters is artificial and uncertain, and the prediction effect is not ideal.…”
Section: Introductionmentioning
confidence: 99%